Design of a multifunctional park for urban regeneration in Barquisimeto city (Gaceta Técnica, 2026)
This project proposes the design of a multifunctional park for the urban regeneration of the Barrio Unión neighborhood in the Iribarren Municipality, Lara State, Venezuela. The primary objective of this plan is to improve the residents' quality of life and contribute to the city's comprehensive development by addressing the various aspects of urban regeneration—ranging from physical infrastructure improvements to the promotion of citizen participation and the strengthening of social cohesion
Keywords: multifunctional park design; Barrio Unión; PDUL